Judicial Considerations in Granting and Rejecting Child Madiyah Support Claims from a Progressive Legal Theory Perspective (A Normative Juridical Study of Decision No. 1172/Pdt.G/2018/PA.Smd. and Decision No. 41/Pdt.G/2014/PA Tkl.) - Reza, M Fahmi; Zahara, Fatimah; Khalid, Khalid (Dinasti Research, 2024)
This study titled